2010
DOI: 10.1242/dev.043885
|View full text |Cite
|
Sign up to set email alerts
|

IGF signaling between blastema and wound epidermis is required for fin regeneration

Abstract: In mammals, the loss of a limb is irreversible. By contrast, urodele amphibians and teleost fish are capable of nearly perfect regeneration of lost appendages. This ability depends on direct interaction between the wound epithelium and mesenchymal progenitor cells of the blastema. It has been known for decades that contact between the wound epithelium and the underlying blastema is essential for successful regeneration. However, the underlying mechanisms are poorly understood. Here, we show that upon amputatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
133
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(137 citation statements)
references
References 50 publications
3
133
0
1
Order By: Relevance
“…Although the role of IGF signaling in regulating normal growth and development is well established, it has only recently become evident that the IGF signaling pathway is often co-opted in various adaptive responses. For example, IGF signaling is increased and has a role in the exercise-induced skeletal muscle hypertrophy in mammals, 51 in fin regeneration upon amputation in zebrafish, 52 and in catch-up growth during re-oxygenation in zebrafish. 53 The results of the present study, along with those mentioned above, suggest that co-option of the ubiquitous IGF signaling pathway in regulating plastic changes of specific tissues in response to environmental factors may be a common theme.…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of IGF signaling in regulating normal growth and development is well established, it has only recently become evident that the IGF signaling pathway is often co-opted in various adaptive responses. For example, IGF signaling is increased and has a role in the exercise-induced skeletal muscle hypertrophy in mammals, 51 in fin regeneration upon amputation in zebrafish, 52 and in catch-up growth during re-oxygenation in zebrafish. 53 The results of the present study, along with those mentioned above, suggest that co-option of the ubiquitous IGF signaling pathway in regulating plastic changes of specific tissues in response to environmental factors may be a common theme.…”
Section: Discussionmentioning
confidence: 99%
“…The robust capacity of the zebrafish (Danio rerio) to regenerate fins, neural tissues (retinal cells, optic nerves, spinal cord), and cardiac muscle has led to the widespread use of this model species for tissue and organ regeneration studies (Chablais and Jazwinska, 2010;Jopling et al, 2010;McCurley and Callard, 2010;Cameron, 2000;Poss et al, 2002Poss et al, , 2003Tawk et al, 2002;Lien et al, 2006;Sherpa et al, 2008). The innate regenerative capability of this species, combined with its relative ease of genetic manipulation, has consequently led to many novel insights into the molecular and cellular regulation of tissue regeneration (Curado et al, 2007(Curado et al, , 2008Davison et al, 2007;Pisharath, 2007;Pisharath et al, 2007;Moss et al, 2009;Pisharath and Parsons, 2009;Zhao et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Genes and cell-signaling pathways that are involved in zebrafish fin regeneration have been previously characterized (Laforest et al, 1998;Tawk et al, 2000;Quint et al, 2002;Padhi et al, 2004;Smith et al, 2006;Jazwinska et al, 2007;Stoick-Cooper et al, 2007a, b;Wills et al, 2008;Yin et al, 2008;Chablais and Jazwinska, 2010). For example, Whitehead et al (2005) reported that the expression of fgf20a, a gene that encodes a member of the fibroblast growth factor family, plays important roles in the initiation of fin regeneration, and that decreases in fgf20a expression result in inhibition of fin regeneration.…”
Section: Introductionmentioning
confidence: 99%